Membuka Peluang Menyelami Pendidikan Multikultural di Era Digital - Falhadi, Mufti Malik; Bahari, Ikrom (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the role of multicultural education in the digital era. This study uses a qualitative approach with a literature study method. The stages of this method include collecting related references through journal publication sources, namely google scholar, selecting and then analyzing concepts and ideas that are important points to be used as the basis for this research. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that multicultural education has an important role in preparing the young generation to face the challenges of the digital era by understanding and appreciating cultural diversity, as well as incorporating local wisdom values in the learning process. In the digital era, the challenges faced by multicultural education are increasingly complex, ranging from the spread of hate speech to the influence of foreign ideologies that can damage national values. Civic education must be strengthened with a strong multicultural foundation. This is important to form a civic awareness that respects diversity, as well as building a sense of love for the homeland and loyalty to the nation. Multicultural-based civic education can utilize technology to broaden students' horizons about cultural diversity and global challenges. Multicultural education in the digital era is not only a challenge but also a great opportunity to create a young generation with character, integrity, and ready to face the changing times